2015
DOI: 10.1016/j.oraloncology.2015.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the relationship between oral chronic graft-versus-host disease and global measures of quality of life

Abstract: Chronic GVHD (cGVHD) is a frequent complication of allogeneic hematopoietic stem cell transplantation (HSCT) and affects multiple organ systems, with the oral cavity being one of the most frequently affected sites. Patients with cGVHD experience reduced quality of life (QOL), yet the specific impact of oral cGVHD on QOL is poorly understood. OBJECTIVE The objective of this study was to characterize the impact of oral cGVHD on global measures of QOL. METHODS QOL data were collected using the FACT-BMT and SF-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 30 publications
(31 reference statements)
1
20
0
Order By: Relevance
“…Data from that study also indicated that physical QoL was lower than and mental QoL comparable with that of the general population. With regards to organ-specific symptoms, the Chronic GVHD Consortium reported the negative impact of GI, hepatic [20], ocular [21], and isolated mouth [19] GVHD on QoL. These analyses were conducted among patients who were diagnosed with GVHD and required systemic immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data from that study also indicated that physical QoL was lower than and mental QoL comparable with that of the general population. With regards to organ-specific symptoms, the Chronic GVHD Consortium reported the negative impact of GI, hepatic [20], ocular [21], and isolated mouth [19] GVHD on QoL. These analyses were conducted among patients who were diagnosed with GVHD and required systemic immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Its diverse symptoms and associated disability are major targets of treatment and care in the long-term follow-up clinic. With a growing awareness, emerging reports on the impact of chronic GVHD on QoL have shown not only that GVHD impairs QoL but also that among patients with chronic GVHD, QoL may differ by severity [11] or affected site [19][20][21]. However, it is still unclear how chronic GVHD clinically affects QoL by affected site and severity, especially in comparison with those who do not have GVHD symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…3. GVHD: this is a condition that can occur after allogeneic bone marrow transplantation [18,60]. The lichenoid changes are common in the chronic type of GVHD, and lichenoid reactions have the highest positive predictive value for chronic GVHD [25].…”
Section: Etiologymentioning
confidence: 99%
“…cGVHD is a systemic disease with multiorgan involvement and a wide range of signs and symptoms with a major impact on patient's life quality (Baker & Fraser, ; DePalo, Chai, Lee, Cutler, & Treister, ; Fraser et al, ). In general, clinical features of cGVHD mimic multiple autoimmune or immune‐mediated conditions such as lichen planus, scleroderma, and systemic lupus erythematosus, characterized by chronic inflammation and fibrosis (Table ) (Baird & Pavletic, ).…”
Section: Chronic Graft‐versus‐host Diseasementioning
confidence: 99%